Older immigrants living in Switzerland and ambivalence related to return around the retirement period. (February 2019) - Bolzman, Claudio A; Bridji, Slim
The aim of this article is to explore the links between former guest workers' attitudes toward return, as they approach retirement age, and ambivalence. More specifically, we seek answers to the following two questions: Do older immigrants modify their intentions toward return around the retirement period? If the answer is positive, we then ask: To which factors are these changes related when looking at intentions to return both before and after retirement? These questions have seldom been analyzed in the sociological literature, and their relation to ambivalence has not yet really been explored. After considering the state of the art, both from a sociology of migration perspective and through a life-course approach, we analyze empirically how older immigrants deal with the question of return. Our data come from a representative survey of approximately 300 older immigrants from Southern Europe (Italy, Portugal, and Spain), aged between 65 and 79 and living in urban Switzerland. Our findings show that (1) while a significant proportion of Italian and Spanish older migrants give up the idea of returning definitively to their country of origin and decide to establish their main residence in Switzerland, among the Portuguese, a significant minority wanted to return before retirement and are still planning to return, expecting to recover full citizenship in their "home" country; (2) changes with respect to return intentions mainly concern former blue-collar workers and white-collar employees; and (3) older immigrants who do not see migration as a positive decision demonstrate more ambivalence about return.